Haplostominae (Copepoda, Cyclopoida) associated with compound ascidians from the San Juan Archipelago and vicinity - Ooishi, Shigeko; Illg, Paul L. (Nippon Publ., 1977)
Special Publication from the Seto Marine Biological Laboratory; Series V December, 1977